KRONİK TİNER İNHALASYONUNUN SIÇAN AKCİĞER VE KARACİĞER DOKULARI LİPİD PEROKSİDASYONLARINA ETKİSİ - ZENGİN ULAKOĞLU, Emel and SAYGI, Atilla and GÜMÜŞTAŞ, M. Koray and ZOR, Erkan and AKKAYA, Asuman and KÖKOĞLU, Emine (Cerrahpaşa Medical Journal, 2019)
Background and Design. We studied the effect of chronic thinner inhalation (during 5 weeks) on lipid peroxidation in the lung and liver of the rats. Additionally, we studied superoxide dismutase (SOD) activities and reduced glutathione (CSH) levels. Results. Significant increases were found in lipid peroxidation (TBA RS) levels of rats which had inhaled thinner compared to those of the control group (p=0.000). As opposed to increases in the TBARS levels, significant decreases in the SOD activities and GSH levels were observed when compared to the rats in the control group (p=0.000). Conclusion. Increases in peroxidative damage due to the reactive oxygen species generation and decreases in the antioxidant capacity may be the cause of some progressive dysfunction in these tissues.